1937
DOI: 10.1098/rspa.1937.0187
|View full text |Cite
|
Sign up to set email alerts
|

The influence of hydrogen and deuterium on the thermal decomposition of diethyl ether in the low pressure region.

Abstract: Richards (1936) found from sound dispersion measurement that at ordinary temperatures, in exciting the lower vibrational states of ethylene, collisions between hydrogen and ethylene molecules were ten times as effective, and collisions between deuterium and ethylene molecules 1∙27 times as effective as collisions between ethylene molecules themselves. This meas that hydrogen is about eight times as effective as deuterium. The Specific effects of foreign gases in facilitating the interconversion of translationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1938
1938
1960
1960

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…REACTION VESSEL (1) ; MIXED CARRIER GAS OF NITROGEN (2 1111T1) AND NITRIC OXIDE (2 IlKtl) For these runs the circulation capillary chosen gave reaction times in the region of 0.6 sec. However, we make no attempt to calculate velocity constants in these runs as the pressure in the reaction vessel is continuously changing due to removal of nitric oxide.…”
Section: Reaction Vessel (3)mentioning
confidence: 99%
“…REACTION VESSEL (1) ; MIXED CARRIER GAS OF NITROGEN (2 1111T1) AND NITRIC OXIDE (2 IlKtl) For these runs the circulation capillary chosen gave reaction times in the region of 0.6 sec. However, we make no attempt to calculate velocity constants in these runs as the pressure in the reaction vessel is continuously changing due to removal of nitric oxide.…”
Section: Reaction Vessel (3)mentioning
confidence: 99%
“…CH, Cunningham and Taylor (6) Gomer and Noyes (12) 25 20 Phibbs and Darwent (28) Thompson and Linnett (37) 37 25 Taylor and Rosenblum (35) Ethane................ Smith and Taylor (32) Isobutane.............. 5.9 Saunders and Taylor (31) Ethylene oxide......... Gomer and Noyes (12) evident from the fact that the fraction (C2He + JCH4)/CO rose above 1 at 250°C. The rates of reaction 22 found by different workers are in good agreement: thus at 182°C.…”
Section: The Photolysis Of Acetonementioning
confidence: 99%
“…Further evidence for the chain character of a number of decomposition reactions is furnished by the work of Staveley and Hinshelwood (188b,189,190) and others (39,55,126,194). They found that while large amounts of added nitric oxide would catalyze the reactions, small amounts caused some inhibition.…”
Section: Rimentioning
confidence: 93%